2014
DOI: 10.15253/2175-6783.2014000200018
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Schools in northeastern Brazil (1943-1975)

Abstract: This is a qualitative, narrative and socio-historical study aimed at analyzing the creation of nursing schools in the Northeast of Brazil (1943-1975). The time frame corresponds initially to the creation of the first school and finally to the year in which all the northeastern states founded at least one training institution for nurses. The data collection happened between April and July 2013 using the collection of the Central Library of the Federal University of Santa Catarina and the Study Group about Nursi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
(8 reference statements)
0
3
0
3
Order By: Relevance
“…Despite the objections, what Nursing is concerned, this structure caused a positive impact, bringing about the growth of teaching with an increased number of places resulting from the emergence of new schools (11) . This detail was proven in RN by the functioning of the Mossoró School of Nurses, the current School of Nursing of the State University of Rio Grande do Norte (FAEN / UERN) and the Nursing Department / UFRN, in 1971 and 1974, respectively (12) . The collected material showed that the nurses of the HOPE Earth Project -Mary Anne Small, Margareth Mein da Costa, Jane Marie Shima, Tyana Payne and Shirley Myers Snowe -served as visiting educators at the Nursing Department / UFRN (13) .…”
Section: Discussionmentioning
confidence: 98%
“…Despite the objections, what Nursing is concerned, this structure caused a positive impact, bringing about the growth of teaching with an increased number of places resulting from the emergence of new schools (11) . This detail was proven in RN by the functioning of the Mossoró School of Nurses, the current School of Nursing of the State University of Rio Grande do Norte (FAEN / UERN) and the Nursing Department / UFRN, in 1971 and 1974, respectively (12) . The collected material showed that the nurses of the HOPE Earth Project -Mary Anne Small, Margareth Mein da Costa, Jane Marie Shima, Tyana Payne and Shirley Myers Snowe -served as visiting educators at the Nursing Department / UFRN (13) .…”
Section: Discussionmentioning
confidence: 98%
“…Esta categoria engloba quatro publicações (6)(7)(8)(9) que abordam as contribuições institucionais para a valorização da identidade profissional do enfermeiro. Os autores centraram os seus estudos em pontos focais da história regional da enfermagem brasileira, tais como as iniciativas institucionais relativas a práticas sociais em prol do resgate da história da profissão (8) .…”
Section: Regionalismo Histórico: Contribuições Das Instituições De Enunclassified
“…Os autores centraram os seus estudos em pontos focais da história regional da enfermagem brasileira, tais como as iniciativas institucionais relativas a práticas sociais em prol do resgate da história da profissão (8) . Entre os artigos analisados, dois manuscritos (6)(7) abordam as contribuições e avanços de instituições de ensino do nordeste brasileiro. Nessa região, em termos de iniciativas de criação da enfermagem profissional, cabe destacar que as pioneiras da enfermagem enfrentaram inúmeras dificuldades, resultantes da falta de compreensão pela necessidade de valores científicos no desenvolvimento da profissão.…”
Section: Regionalismo Histórico: Contribuições Das Instituições De Enunclassified
“…Thus, care practices, such as the provision of food or substances for curative purposes to cope with diseases, have a cultural character, transmitted from generation to generation. However, beginning in the nineteenth century, care practices to prevent or cure diseases underwent a process of professionalization, coming to be considered an attribute of health professionals, especially those of nursing (1)(2) .…”
Section: Introductionmentioning
confidence: 99%